Children Resilience In Dealing With Parental Divorce Based On the Ability to Regulate Emotions And Optimism - Febriady Hutauruk; Riska Ahmad; Alwen Bentri (International Journal of Research in Counseling and Education, 2020)
Resilience is the ability of an individual to rise from adversity or the problems faced. It is needed in dealing with various bitter events such asparental divorce. To attainresilience, children need emotional and optimistic arrangements in dealing with problems. The purpose of this study, therefore, wasto examinechildren's resilience in the face of parental divorce based on the regulation of emotions and optimism. This wasa case study conducted in the city of Padang. The subjects in this study were two students with the criteria of having divorced parents in lessthan seven months or with the provision that the divorce occurred within the study period. Data analysis techniques usedwereinteractive models. The results showed resilience in children was different evenwhilefacing the same problem, such as parental divorce. For instance, one of the respondents,OT, had an excellent emotional arrangement while facing the parental divorce, while the other one, BT,was poor. The level of optimism in children also declined due to parental divorce.